Educational assessment in virtual world environments - Reiners, Torsten; Gregory, S.; Dreher, Heinz (Curtin University, 2011)
Facilitating and empowering learners and teachers through technology has primarily concentrated on content and management aspects rather than on assessments aspects of the education enterprise. ecent developments in virtual world technology have sparked a raft of projects exploring the possibilities to enhance learning outcomes. In this article, automated support for educational assessment is focussed on via three case studies implemented in Second Life, the 3D virtual world implemented by Linden Labs. This paper discusses the assessment tasks, the methods used and provides an analysis of our results. The University of Hamburg case study involves scenario-based software development projects. The Curtin University case study focuses on simulating the business processes of the Automated Assessment Lab, which provides automated assessment opportunities to staff of the Curtin Business School, and in which a virtual world model of the entire assessment life cycle is created. A third case study from the University of New England, VirtualPREX (Virtual Professional Experience), explores self, peer and academic formative and summative assessment in virtual world role-play scenarios. Each case study comprises a description of intent and implementation, followed by evaluative comments from the role players, providing insight into the benefits that may accrue from the use of virtual world technology for students, teachers and educational administrators.